Registration of 'Lustre' durum wheat. Issue 3 (9th August 2022) - Hogg, Andrew C.; Carr, Patrick; Eberly, Jed; Chen, Chengci; Kowatch‐Carlson, Calla; Crutcher, Frankie; Lamb, Peggy; McNamara, Kyla; Haney, Eleri; Kephart, Ken; Smith, Valerie; Dykes, Linda; et al.
Abstract: 'Lustre' (Reg. no. CV‐1193, PI 695072) is a spring durum wheat [ Triticum turgidum L. ssp. durum (Desf.)] developed by the Montana Agricultural Experiment Station and released in 2020. Lustre was bred using the single seed descent method and was selected for its yield performance under dryland conditions across Montana, low grain Cd accumulation, good pasta firmness, high grain protein, high yellow semolina color, and low semolina ash. Lustre performs well in both the north central and northeast regions of Montana, where most Montana durum is produced and intended for pasta production. Lustre has similar stripe rust tolerance and susceptibility as top‐grown durum cultivars in the state with susceptibility at the seedling stage and high‐temperature adult‐plant resistance. Lustre is moderately susceptible to Fusarium head blight like other durum cultivars. Lustre is resistant to the predominant races of stem and leaf rust and is moderately tolerant to fungal leaf spot complex. Lustre is approximately 89 cm tall, with a yellow green color and a heading date 1 d later than the cultivar 'Mountrail'. Lustre has an erect flag leaf and an erect tapering head having white glumes and awns. Core Ideas: Lustre is a new durum wheat. Lustre yields well in north central and northeast Montana. Lustre is a standard height durum with white glumes and awns. Lustre has low grain Cd content, high grain protein, and high yellow semolina color.